Gemcitabine combined with baicalein exerts antiviral activity against PEDV by inhibiting the entry and replication phases - Yingge Zheng; Yanfei Zhang; Fangying Xiong; Dehua Luo; Yuxiang Wang; Yijia Zhang; Dengguo Wei (Animal Diseases)
Abstract Cocktail therapy significantly reduces the development of resistance to individual medications due to viral mutations. However, for effective inhibition of a particular virus, a customized approach to combination pharmacotherapy may be essential. Porcine epidemic diarrhea virus (PEDV) is a member of the Coronaviridae family, whose genome consists of a single strand of positive-sense RNA and has evolved into multiple epidemic lineages with no available drugs in clinical practice. In this study, we found that the nucleoside analog gemcitabine decreased the titer of PEDV, with a median effective concentration (EC50) of 3.12 μM, thereby inhibiting viral replication. The natural product baicalein acts by targeting the early entry stage and directly inactivates the virus, with an EC50 of 5.02 μM. A notable synergistic effect was observed with the combination of 1 μM gemcitabine and 1.5 μM baicalein. This study demonstrated that the strategic use of a drug combination targeting both the replication and entry phases of the PEDV lifecycle can effectively inhibit viral proliferation.